Peripheral Display in Virtual Reality Environments involves Higher Cognitive Demands Compared to Centered Display during Dual-Tasking. (September 2022) - Bouzar, Moncef; Bryce, Marquessa; Castillo, Segny; Cortez, Damian; Doucette, Olivia; Garcia, Bayron; Ho, Andy; Ito, Kara; Kim, Chris; Lansdell, Kelly; Soangra, Rahul
Peripheral displays may require higher attention allocation compared to centered displays. This study investigated how cognitive load with peripheral dual-tasking affected gait variability in healthy young adults compared to centered dual-tasking. Eleven healthy young adults (23.8±1.25 years) participated in the experiment. Participants performed three trials of three different tests while walking on the treadmill. The tasks were randomly assigned as i) normal walking without dual tasking, ii) walking with a centered cognitive arithmetic test or centered dual-tasking (DTC) and iii) walking with peripheral cognitive arithmetic test or peripheral dual-tasking (DTP). Gait parameters were evaluated for all three task conditions. We found step width significantly increased during DTP compared to the control walking condition (p<0.05). Our results revealed that DTP was challenging even for healthy young adults and thus leading to adaptations in step width. Our results show that DTP has clinical diagnostic values in revealing subtle gait deviations and can potentially be used to assess Parkinson's disease and post-concussion disorders.